Work Organisation, Forms of Employee Learning and National Systems of Education and Training. (June 2016) - Lorenz, Edward; Lundvall, Bengt‐Åke; Kraemer‐Mbula, Erika; Rasmussen, Palle
Abstract : This article uses a multi‐level framework to investigate for 17 European nations the links between forms of work organisation and style of employee learning at the workplace on the one hand, and the characteristics of national educational and training systems on the other. The analysis shows that forms of work organisation characterised by relatively high levels of employee discretion and learning are more likely to be adopted in nations with broad‐based systems of education and training that recognise the value of both academic and vocational training and provide ample opportunities for continuing adult education. Furthermore, it shows that employees with low levels of formal education have better access to jobs involving organisational learning in countries with more developed adult education systems. The results point to the need to balance policies designed to increase tertiary education rates with a commitment of resources at both the EU and national levels to develop broad and inclusive systems of lifelong learning.